การพัฒนาเจลอาบน้ำสูตรผสมสมุนไพรสู่มาตราฐานผลิตภัณฑ์ชุมชน - นวลใย, ธเนศวร (Area Based Development Research Journal, 2016)
บทคัดย่อไม่สมบูรณ์ Development of mixed herbs shower gel toward the community product standard Shower gel mixing herbs had been developed. Five herbs; sappan, carrot, pea, curcumin and aloe vera were tested for shower gel ingredients. It was found that aloe vera was suitable for these formulations. Moreover, the aloe shower gel mixing could be formulated all seven scents smell; jasmine rice, sakura, tulip, tear of flower, jasmine, marine fresh, and lavender. The color and flavor did not make the physical properties of shower gel changeable. The pH and free alkaline of these shower gels were tested under TIS. 1403-2551. These knowledges were passed on Koh-Tao and other communities. The recipients were satisfied with the aloe shower gel formulated and upgraded this herb gel to become community products.